How reliable is renal ultrasound to measure renal length and volume in patients with chronic kidney disease compared with magnetic resonance imaging?. (January 2020) - Braconnier, Philippe; Piskunowicz, Maciej; Vakilzadeh, Nima; Müller, Marie-Eve; Zürcher, Emilie; Burnier, Michel; Pruijm, Menno
Background: Renal length, volume, and parenchymal thickness are important clinical parameters, yet data concerning the accuracy and reproducibility of ultrasound (US)-based renal length and volume assessment in patients with chronic kidney disease (CKD) are scarce. Purpose: To establish whether renal length, volume, and parenchymal thickness can be reliably measured with renal US in patients with CKD. Material and Methods: All participants underwent renal US, immediately followed by 3-T magnetic resonance imaging (MRI). Renal length, width, transverse diameter, and parenchyma thickness were measured with both methods; renal volume was calculated using the ellipsoid formula. A total of 45 patients with CKD (eGFR [mean ± SD] 57.4 ± 4.4 mL/min/1.73 m 2 ) and 46 participants without CKD (eGFR 97.0 ± 2.4 mL/min/1.73 m 2 ) were included. Results: US-measured renal length correlated strongly with MRI-measured renal length in no-CKD patients (Spearman's r = 0.83 and 0.85 for the right and left kidney, respectively; P < 0.005) and CKD patients (r = 0.89 and 0.92 for the right and left kidney, respectively; P < 0.005). There was a significant but weaker correlation between MRI- and US-measured right and left renal volume (r = 0.72, P < 0.005) in no-CKD (r = 0.74 and r = 0.72, respectively; for both: P < 0.005) and CKD patients (r = 0.83 and 0.85, P < 0.005). Weak to moderate correlations were found for parenchyma thickness for the right (CKD group: r = 0.29, no-CKD: r = 0.23; for both: P < 0.05) and left kidney (CKD: r = 0.52, no-CKD group: r = 0.37, P < 0.05). Both intra-observer (Pearson's correlations of 0.82 for the right and 0.89 for the left kidney) and inter-observer (Lin's correlation coefficient of 0.90 for the right and 0.82 for the left kidney) reproducibility of US-assessed renal length was high. Conclusions: US-based assessment of renal length in CKD patients is comparable to MRI measures. Both intra- and inter-observer reproducibility of US-assessed renal length in CKD patients are high. Measurements of US renal volume and parenchymal thickness should, however, be interpreted with caution.